Domestic dog attacks on livestock referred to a Veterinary Teaching Hospital - Gonzaga, Mariana da Costa; Borges, José Renato Junqueira; Alves, Teresa Souza; Sousa, Davi Emanuel Ribeiro de; Castro, Márcio Botelho de; Câmara, Antonio Carlos Lopes (Frontiers in Veterinary Science, 2024)
Losses and the economic impact of dog attacks (DAs) on livestock are often overlooked and include factors such as decreased production, expenses for treatment and handling, and death of injured animals. This study evaluated the epidemiology, therapeutic, and pathological findings of DAs in livestock over an 11-year survey in the records of farm animals referred to a Veterinary Teaching Hospital. Livestock attacked by dogs included 31 sheep, 11 horses, three cattle, three goats, and two pigs, totaling 50 animals. Anatomical locations injured by dog bites were identified as head/neck, thoracic/pelvic limbs, abdomen/flank, rump/tail, and multiple affected regions (two or more bite sites). Additionally, the severity of the injuries was classified in four degrees adapted from the classification of dog bite injuries in children. Most livestock presented Grade 1 (26%) and 2 (28%) injuries, while Grade 3 and Grade 4 injuries were observed in 46% of DAs. Thirty-five animals (70%) were discharged, nine (18%) died, and six (12%) were humanely euthanized. DAs may represent a significant cause for referring livestock species to clinical care, severe injuries, and a considerable number of deaths. We are providing information on DAs in livestock for the first time in Midwestern Brazil.